Mediation and the Contradictions of Representing the Urban Poor in South Africa: The Case of SANCO Leaders in Imizamo Yethu in Cape Town, South Africa - (:unkn) unknown (My University, 2014)
In exploring the nature of local leadership, we want to focus on the notion of mediation, as the concept invokes the idea of some kind of ‘third-party’ representation of the politically marginalised. Further, in South Africa, like many of the southern contexts (Chatterjee 2004, Yiftachel 2009, Piper and Lieres 2011, Journal of Asian and African Studies 2011), there is a strong case that the (black) urban poor struggle to access the state. Indeed, the need ‘to remedy the inequality […] in access to the state’ is, we argue, particularly important in South African low-income neighbourhoods for at least three reasons. The first is the fragmentation and complexity of the state apparatus and operations, partly linked to its system of three ‘spheres’ (not ‘tiers’) of government (national, provincial and local) where overlapping responsibilities are not clearly attributed and hierarchised. This fragmentation of the state has been increased after the implementation of New Public Management principles in local government in the 2000s that have further blurred the roles, functions and responsibilities of multiple parastatal agencies, corporations and organisations in charge of public service delivery and management. The second is the dysfunctional and disappointing institutional participatory structures and channels set up at the local government level (Transformation 66/67 2008), often leading to civil society groups ‘inventing’ other means of getting heard by the state. These include mass protests, which can turn violent (Alexander 2010; Von Holdt et al. 2011), and using party connections to replace failing and fragmented local government channels (Bénit-Gbaffou 2012). Third are the high levels of popular expectation towards a South African state that has adopted the figure of the ‘developmental state’ (Van Donk et al. 2008, Parnell and Pieterse 2010) and has engaged since 1994 in ambitious state-driven mass delivery policies (housing
Keywords: African Research